A simplified compact model of miniaturized cross-shaped CMOS integrated Hall devices - 黄海云 王德君 李文波 徐跃 秦会斌 胡永才 (Journal of semiconductors, 2012)
A simplified compact model for a miniaturized cross-shaped CMOS integrated Hall device is presented. The model has a simple circuit structure,only consisting of a passive network with eight non-linear resistors and four current-controlled voltage sources.It completely considers the following effects：non-linear conductivity,geometry dependence of sensitivity,temperature drift,lateral diffusion,and junction field effect.The model has been implemented in Verilog-A hardware description language and was successfully performed in a Cadence Spectre simulator.The simulation results are in good accordance with the classic experimental results reported in the literature.